ChemInform Abstract: Nickel‐Catalyzed Regio‐ and Diastereoselective Intermolecular Three‐Component Coupling of Oxabicyclic Alkenes with Alkynes and Organoboronic Acids. Issue 25 (3rd June 2013) - Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract A highly regio‐ and diastereoselective three‐component reductive coupling reaction affording exo‐5, 6‐disubstituted 7‐oxanorbornene derivatives in good to excellent yields is reported.